Recent advances in the application of deep eutectic solvents as sustainable media as well as catalysts in organic reactions. Issue 60 (2nd July 2015) - Liu, Peng; Hao, Jian-Wu; Mo, Li-Ping; Zhang, Zhan-Hui
<x xml:space="preserve">Abstract</x> This review highlights the recent advances using deep eutectic solvents (DESs), deep eutectic ionic liquids (DEILs), low-melting mixtures (LMMs) or low transition temperature mixtures (LTTMs) as green media as well as catalysts in organic reactions.